2022
DOI: 10.1186/s12953-022-00190-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanobody as therapeutics target for EGFR-positive colorectal cancer therapy: exploring the effects of the nanobody on SW480 cells using proteomics approach

Abstract: Background The epidermal growth factor receptor (EGFR) overexpression is found in metastatic colorectal cancer (mCRC). Targeted molecular therapies such as monoclonal antibodies (mAbs) and tyrosine kinase inhibitors (TKI) are becoming more precise, targeting specifically for cancer therapeutics. However, there are adverse effects of currently available anti-EGFR drugs, including drug-resistant and side effects. Nanobodies can overcome these limitations. Our previous study has found that cell-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Suppression of binding sites of EGFR signaling at the level of extracellular receptor or tyrosine kinase intracellular activity may inhibit EGFR expression networks and thus improve patient outcomes ( Kitamura et al ., 2020 ; Wingert et al ., 2021 ). Several authors have suggested that the increased expression of EGFR has negative impacts ( Kwon et al ., 2018 ; Hashmi et al ., 2019 ; London and Gallo, 2020 ), while others maintain the opposite ( Pidugu et al ., 2019 ; Feng et al ., 2020 ; Lamtha et al ., 2022 ). However, meta-analysis data summarizing the results of various studies show that exposure to EGFR is not an independent predictor of survival in various diseases ( Yang et al ., 2019 ; Nastały et al ., 2020 ; Atef et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of binding sites of EGFR signaling at the level of extracellular receptor or tyrosine kinase intracellular activity may inhibit EGFR expression networks and thus improve patient outcomes ( Kitamura et al ., 2020 ; Wingert et al ., 2021 ). Several authors have suggested that the increased expression of EGFR has negative impacts ( Kwon et al ., 2018 ; Hashmi et al ., 2019 ; London and Gallo, 2020 ), while others maintain the opposite ( Pidugu et al ., 2019 ; Feng et al ., 2020 ; Lamtha et al ., 2022 ). However, meta-analysis data summarizing the results of various studies show that exposure to EGFR is not an independent predictor of survival in various diseases ( Yang et al ., 2019 ; Nastały et al ., 2020 ; Atef et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since cancer is a compacted and multiple genes involved disease, drugs that act at multiple targets can improve efficacy and lower drug resistance and are considered as the future of worthy anticancer drug development 5 . One of the most efficient and known manner in cancer therapy, is targeting protein kinases due to their vital role in regulation of various cellular signal transductions and activities, such as, proliferation, differentiation, apoptosis, metabolism and transcription 6–8 .…”
Section: Introductionmentioning
confidence: 99%